Symptoms of attention deficit hyperactivity disorder in patients with systemic lupus erythematosus. (December 2015) - Gao, Y; Lo, Y; Mok, M Y
Objectives: Cognitive function and mood disturbance are common in patients with systemic lupus erythematosus (SLE). This study aims to examine whether SLE patients have more features of adult attention deficit hyperactivity disorder (ADHD) and their relation to anxiety and depressive symptoms. Methods: Symptoms and clinically significant items of the inattention and hyperactivity/impulsivity domains of ADHD were examined in Part A and Part B by the screening instrument of the ADHD Self-Reported Scale (ASRS), respectively. Anxiety and depressive symptoms were measured by HADS-A and HADS-D, respectively. Results: There were no differences in symptom scores of inattention and hyperactivity/impulsivity between inactive SLE patients ( n = 117) and age- and sex-matched controls ( n = 64). However, SLE patients had more clinically significant items in the inattention domain compared with controls ( p = 0.006), particularly among those who had previous cerebral involvement ( p = 0.004). Patients who had psychiatric diseases had more clinically significant items in the hyperactivity/impulsivity domain ( p = 0.006). Possible ADHD was found in 7.7% of SLE and 6.3% of healthy individuals ( p = 1.00) by the screening tool. Patients with higher inattention symptom scores were more likely to be unemployed but not for duration of education and smoking habit. Anxiety and depressive symptoms correlated with ADHD symptoms. HADS-A was an independent predictive factor for clinically significant symptoms of inattention ( p < 0.001) and hyperactivity/impulsivity ( p = 0.04) by logistic regression. Conclusion: Inactive SLE patients, particularly those who had previous cerebral lupus, had more clinically significant symptoms of inattention but not hyperactivity/impulsivity reflecting underlying cognitive impairment. Anxiety and depressive symptoms were common confounders for ADHD-like symptoms.